Traditional Medicine of the Biak Tribe in Opuri Village, Biak Regency Papua - Womsiwor, Priskila Septina; Flassy, Marlina; Idris, Usman; K. Frank, Simon Abdi (Science Midwifery, 2024)
This article aims to describe and analyze the mechanism of traditional medicine practiced by the Biak people in Opuri Village, and the factors that determine why people still often use traditional medicine methods as an alternative to efforts to cure diseases suffered by them. The theoretical approach used is the perspective of medicine anthropology to examine the treatment of diseases that are naturalistic and personalistic in nature traditionally based on the ethnoscience of local communities. The research method used is descriptive qualitative, with an ethnographic approach. Selection of informants was done by purposive sampling. The data collection techniques used were interviews and field observations as well as literature review. The research instrument used is a sound and image recorder to help facilitate the process of processing field data. The stages of data analysis include data reduction, data presentation, conclusion drawing and verification. The results showed that the use of traditional medicine methods is still carried out by the Biak people in Opuri Village because it aims to treat personalistic diseases, so that not only physical treatment is needed, but also metaphysical. Although there are also those related to naturalistic diseases. Meanwhile, the factors behind the use of traditional medicine methods are social, economic, cultural, and comfort factors